Comparative Analysis of Anti-essentialist and Institutional Theories of Art - Janicki, Jędrzej (Hybris, 2019)
The aim of this article is to assess critically and compare Morris Weitz’s anti-essentialist theory of art to George Dickie’s institutional one. The comparison is based on a so-called Auschwitz incydent. The article shows both differences and similarities in described theories. The scope of interest is limited to the XXth Century art, since works from this period question traditionally understood meaning of art. In the article are also briefly mentioned other concepts of art (e.g. Clive Bell’s) and the idea of artworld proposed by Arthur C. Danto, which served later as basis for other theories. The article shows that the two described theories are rather complementary than contradictory to each other.